THE EFFECT OF FINANCIAL LITERATURE AND SELF CONTROL ON CONSUMPTION BEHAVIOR (STUDY ON STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA) - Sari, Maya; Adilla Bahri Lubis, Nur; Jufrizen, Jufrizen (CV. Radja Publika, 2021)
The purpose of this study was to determine and analyze the effect of financial literacy on consumptive behavior of students with financial concentration in 2017 in the Management Study Program, Faculty of Economics and Business, Universitas Muhammadiyah Sumatera Utara. to find out and analyze the effect of self-control on consumptive behavior. Students with 2017 financial stambuc concentration in Management Study Program, Faculty of Economics and Business, Universitas Muhammadiyah Sumatera Utara. This study uses a quantitative research approach. The data analysis technique in this study uses multiple linear analysis techniques. The results of the study indicate that partially there is a significant effect of the Financial Literacy variable on the Consumptive Behavior of the Students of the Faculty of Economics and Business, Universitas Muhammadiyah Sumatera Utara. The results of this study conclude that partially there is a significant effect of the variable Self-Control on Consumptive Behavior in Students of the Faculty of Economics and Business, Universitas Muhammadiyah Sumatera Utara. Economics and Business Universitas Muhammadiyah Sumatera Utara.